Characteristics of novel Myco-coagulant for reducing turbidity in water treatment. - Mamun, Abdullah Al; Jebun, N.; Alam, Md. Zahangir; Ahmad Raus, Raha (2016)
Chemical coagulants are widely used in water and wastewater industry. These chemical based coagulants and flocculants have various types of effects on the aquatic environment. The search and use of biodegradable natural coagulants are on-going for centuries. Researchers are investigating various types of plants, fungi, bacteria, etc. to discover a more environmentally friendly coagulants. In this research, several species of fungi were isolated and studied for potential bio-coagulant. One species of the fungi investigated produced novel myco-coagulant, which was characterised with regard to synthesis and application to reduce turbidity of water. The myco-coagulant showed good stability in wide range of pH at 4 to 8 and temperature at 4 to 45oC. The supernatant was used as coagulant, which was able to reduce 90% turbidity removal from kaolin suspension. The myco-coagulant consisted of protein 0.2954 mg/ml, total sugar 5.17 mg/ml and total carbohydrate 0.237 mg/ml. Fourier-transform infrared spectroscopy (FTIR) analysis revealed that discovered myco-coagulant contained hydroxyl, amide, alkyne and alkyl halide groups. The average zeta potential value of myco-coagulant was -7.0 mV while kaolin suspension was -25.2 mV. These findings suggest that charge neutralization is the main coagulation mechanism of new myco-coagulant The myco-coagulant also exhibited ability to reduce the turbidity of water pretty quickly, which was about 5 minutes of settling time.